PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP SIKAP BELAJAR (PADA MATA PELAJARAN AQIDAH AKHLAK SISWA KELAS VII B) DI MTs NEGERI 1 KUANTAN SINGINGI - Yusneti Yusneti; Helbi Akbar; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2023)
This study aims to determine the effect of the application of the Jigsaw Cooperative Learning Model on Learning Outcomes in Aqidah Akhlak Subjects for Class VII B students at MTs Negeri 1 Kuantan Singingi. Based on the results of data collection by means of observation, questionnaires and documentation, then the data were analyzed using the Simple Linear Analysis formula and using SPSS 21.0 data, it can be concluded that: There is an effect of the application of the Jigsaw Cooperative Learning Model on Learning Outcomes in Aqidah Akhlak Subjects Class VII B at MTs Negeri 1 Kuantan Singingi is in accordance with the coefficient of determination (R Squere) of 0.014 (is the square of the correlation coefficient, or 0.119 x 0.119 = 0.014161). The magnitude of the coefficient of determination (R Square) of 0.014 is equal to 1.4%, this number means that the application of the Jigsaw Cooperative Learning Model in Aqidah Akhlak subjects affects the learning outcomes of class VII B students by 1.4%. While the rest is influenced by other variables.